An overview of the evolution of russian space stations and its development prospects - A. D. Starinets (Космические аппараты и технологии, 2024)
The history of the development of Russian orbital space stations and prospects for the future development of this field are presented. The significance of their use for the exploration of both near and distant outer space is discussed. A brief overview of Soviet and Russian space programs related to the development of orbital stations is provided. Trends in the development of individual orbital stations have also been analyzed, as well as implementation errors and methods for their resolution. The scientific importance of the Mir space station and experiments conducted on it are discussed. The results of 15 years of operation have been summarized. The reasons for the establishment, stages of development, current status, ongoing research and experiments of the International Space Station are analyzed, as well as future plans for its operations. In addition, the current state of development of the Russian orbital station, the stages of its evolution, planned scientific experiments, and the long-term prospects for the use of orbital stations are considered. This material can be utilized to compose a dissertation on the historical significance and scientific relevance of Russian orbital missions, as well as to undertake research on error analysis, comparative analyses with other space programmes, and the advancement of new technologies for upcoming missions.